If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + 40 = 15 + 26 Reorder the terms: 40 + 9x = 15 + 26 Combine like terms: 15 + 26 = 41 40 + 9x = 41 Solving 40 + 9x = 41 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-40' to each side of the equation. 40 + -40 + 9x = 41 + -40 Combine like terms: 40 + -40 = 0 0 + 9x = 41 + -40 9x = 41 + -40 Combine like terms: 41 + -40 = 1 9x = 1 Divide each side by '9'. x = 0.1111111111 Simplifying x = 0.1111111111
| 6r+6+4=6 | | 4x(x+3)=32 | | 4(X-9)+2=2x-8+X | | -2=m^16 | | -5(-2x+3)-1=8+15x | | 19x-5x=168 | | 1/2y=6/1 | | 5g=3g+10 | | a^29=5 | | 16=4V-8 | | x^2-8x+y^2-8y=4 | | whatisx-27=62forx | | x^2+ax+3=0 | | N^2+10n=16 | | 3-19=9x-2-8x | | 24x-12y=25 | | 15=5(m-7) | | y=(3+2k)x | | 2x+22=10-74 | | -10=-14a+14a | | 3+x-11=3 | | 9+2(y-3)=12 | | (35+3x+9y)-(5x+7y+27)=0 | | -2x+12=2x | | 4y^2-y+y^2= | | 6-5c=-28 | | T=6s+21.75 | | 8+2ln(x)=3 | | 6x+8=2x^2 | | f(x)=5x(x^2-2x-1) | | Fx+gx=j | | (18+5x+8y)-(2x+9y+40)=0 |